Press-mud as Nutrient and Amendment for Sodic Water Irrigation in Sustaining Rice-Wheat System - Yaduvanshi, N. P.S. (Indian Farming, 2015)
Results of long term experiment have shown that rice and wheat yeilds increase significantly with integrated use of gypsum or press-mud, alongwith 100% recommended levels of inorganic NPK fertilizers. Organic amendments like press-mud have been found effective in improving and maintaining fertility of sodic soil under sodic water irrigation.